Pengaruh penerapan PSAK 73 terhadap kualitas laba - Anisa, Ayu Nur; Yanti, Harti Budi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze and conduct empirical tests on the application of PSAK 73 and its effect on the earnings quality of open entities on the Indonesian Stock Exchange (IDX). The study was carried out through a quantitative methodology. Then the data used in the study is secondary data adapted to the IDX. The population in this study is all public entities listed on the Indonesian Stock Exchange (IDX) in the 2019-2021 period, with a total of 102 companies with 306 units of analysis. The sampling methodology in this study used purposive sampling. The method of research in this study is multiple regression. The results of hypothesis testing in this study show that the results of the variables in PSAK 73, namely usufructuary assets and interest expense, have a positive effect on earnings quality. Meanwhile, rental liabilities harm earnings quality and depreciation expense has no significant impact on earnings quality.